Pengaruh Profitabilitas Terhadap Harga Saham (Studi pada Perusahaan Financial Technology yang Terdaftar di NASDAQ) - Andrea Octavianti Hariyanto (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2023)
This study aims to obtain an overview of the profitability of stock prices in financial technology companies listed on the NASDAQ. The type of research used is descriptive and verification research with explanatory research methods. The sampling technique in this study is purposive sampling technique with a total sample of 6. Financial technology companies listed on the NASDAQ are the objects in this study. The data analysis technique used in this study is a panel data regression analysis technique with data processing applications using the Eviews 12 program. This study obtained findings showing that profitability has a positive effect on stock prices. Based on the results of this study, it can be concluded that the higher the level of profitability achieved by the company, the level of stock prices will increase